2018
DOI: 10.1123/jsm.2017-0306
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Leadership Networks in the NCAA: Analyzing Affiliation Networks of Senior Woman Administrators and Athletic Directors

Abstract: The purpose of this study is to examine and compare the informal networks of both senior woman administrators (SWAs) and athletic directors (ADs) within National Collegiate Athletic Association Division I institutions. Drawing on extant literature citing the underrepresentation of women in sport leadership positions, we incorporate a network approach to build and analyze affiliation networks of SWAs and ADs. Guided by the framework of Leadership in Networks, we argue that the social structures within which ADs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Several co-existing and often contradictory components of gendered selection practices have also been outlined, including a tendency towards careerism, informalism (i.e. operation of ‘old boys’ networks’), an emphasis upon entrepreneurialism and financial acumen, paternalism and a tendency towards authoritarianism (Katz et al, 2018; Knoppers and Anthonissen, 2005). Professional managerial experience is also considered important in some settings (Hovden, 2000a).…”
Section: Research At the Macro-levelmentioning
confidence: 99%
“…Several co-existing and often contradictory components of gendered selection practices have also been outlined, including a tendency towards careerism, informalism (i.e. operation of ‘old boys’ networks’), an emphasis upon entrepreneurialism and financial acumen, paternalism and a tendency towards authoritarianism (Katz et al, 2018; Knoppers and Anthonissen, 2005). Professional managerial experience is also considered important in some settings (Hovden, 2000a).…”
Section: Research At the Macro-levelmentioning
confidence: 99%
“…Female coaches struggle to build networks and obtain mentors (Greenhill, Auld, Cuskelly, & Hooper, 2009;Walker & Bopp, 2010) due to the male-dominated nature of the environment. Strong evidence of an "good ole boys" club and the absence of a similar network for women has been identified as well (Katz, Walker, & Hindman, 2018;Taylor & Hardin, 2016). In nonsport environments, mentorship has shown to improve job satisfaction, career mobility, and career commitment (Chao, Walz, Gardner, 1992;Høigaard & Mathisen, 2009).…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…The issue of mentorship has often been associated with women being excluded from the old boys' club, a network of predominantly White men disseminating resources and opportunities to other White men, perpetuating homologous reproduction of this group as leaders (Shaw, 2006 ; Walker and Bopp, 2011 ; Walker and Sartore-Baldwin, 2013 ; Singer and Cunningham, 2018 ; Lapchick et al, 2019b ). For example, Katz et al ( 2018 ) found that the SWA network is less cohesive compared to male-dominated athletic director (ADs) and consequently the appointment of an SWA was found not to be the most successful path to AD ascension because these women were “detached from the center of the network as only a single female AD” (McDowell and Cunningham, 2009 ; Katz et al, 2018 , p. 145). The aforementioned multi-level issues [micro- (interpersonal), meso- (institutional), and macro-levels (association-wide and societal)] grounded in sexism are also prevalent in the institutional racism within the NCAA, which underscores the interconnectedness between oppressive ideologies.…”
Section: Barriers Facing Womenmentioning
confidence: 99%
“…It has been well-documented how the NCAA was founded upon racist and sexist principles whereby racial minorities and women were largely excluded from leadership roles during the early twentieth century (Cooper et al, 2017 ; Katz et al, 2018 ). In recent years, several scholars have promoted culturally responsive leadership as a solution to the problems of racial inequities within K-20 schooling systems (Gay, 2002 ; Johnson, 2007 ).…”
Section: Culturally Responsive Leadershipmentioning
confidence: 99%